Non-collinear libration points in CR3BP when less massive primary is an heterogeneous oblate body with N-layers - Idrisi, M Javed; Shalini, Kumari (International Journal of Advanced Astronomy, 2016)
In the present paper, the existence of non-collinear libration points has been shown in circular restricted three-body problem when less massive primary is a heterogeneous oblate body with N-layers. Further, the stability of non-collinear libration points is investigated in linear sense and found that the non-collinear libration points are stable for the critical value of mass parameter µ ≤ µcrit= µo – 3.32792 k1 – 1.16808 k2.